The murder room : the heirs of Sherlock Holmes gather to solve the world's most perplexing cold cases - Capuzzo, Mike (New York : Gotham Books, 2010)
Documents the efforts of the Vidocq Society, an elite trio of gifted investigators, to solve such notorious cold cases as those of JonBenet Ramsey, the Butcher of Cleveland, and Jack the Ripper, and details their work with the world's top forensic specialists
The connoisseurs of murder -- The man who got away with murder -- The knights of the Caf Ťable -- A little child shall lead them -- Cops and robbers -- The man who saw dead people -- Shades of the dark knight -- Guardians of the city -- Cold eyes from the past -- On the trail of the assassin -- Death of a B-girl -- The visual detective -- The man with the bad stomach -- On the trail of the warlock -- The reluctant knight errant -- The perfect mass murder -- The mask of the invisible man -- The return of Vidocq -- The gathering of detectives -- Busted -- The detective of souls -- The death artist -- Dreams of Morpheus -- A case they can't let go -- The butcher of Cleveland -- Imploring God -- The end of the affair -- Catch me if you can -- The case of the shoeless corpse -- The case of the prodigal son -- The sage of Scotland Yard -- Think therefore on revenge -- Murder in the cathedral - - What I want to hear are handcuffs -- The consulting detectives -- Take me to the psychopath -- The stranger in Biddle House -- City of brotherly mayhem -- Wrath sweeter by far than the honeycomb -- The worst mother in history - - The boy who never died -- The eight babies called "it" - - Murder in triplicate -- From heaven to hell -- The descent -- In the world which will be renewed -- "Congratulations, you've found your killer" -- Interrogation -- The haunting of Mary -- The case of the missing face -- The killer angels -- The ghost -- The ninth circle of hell -- Death in the time of bananas -- The miracle on South Street -- Knights of the round tables
Includes bibliographical references
Keywords: Vidocq Society; Murder -- United States -- Case studies